THE EFFECT OF THE INITIAL CONCENTRATION AND FLOW RATE OF STRONTIUM WASTE ON THE ADSORPTION ABILITY OF HKUST- 1 USING THE FLOW METHOD - Dewanta, Reinaldo Brian (2023)
Strontium-90 is a nuclear fission product with a half-life of 28.79 years (<30 years). Strontium is highly dangerous if it enters the body because it emits beta rays and accumulates in the bones, particularly the spine. Therefore, it is necessary to separate strontium from the solution, and one way to do this is through adsorption. HKUST-1, a porous crystalline material, shows great potential as an efficient adsorbent for heavy metal uptake. This research investigated the adsorption capability of HKUST-1 for radioactive waste. The adsorption process was carried out using a column system, which is commonly used in industrial applications with a top-to-bottom flow. The concentration of Sr(NO3)2 liquid waste was varied at 25, 30, and 40 mg/L, and there were also variations in the waste flow rate at 1, 3, and 5 mL/min. Atomic absorption spectroscopy (AAS) testing was performed to analyze the adsorption output. The research results that increasing the initial concentration of the waste led to an increase in the adsorption capacity, as well as the greater the waste flow rate, the higher the adsorption capacity. The optimum value were obtained at an initial concentration of 40 mg/L and a flow rate of 5 mL/min.